Yersinia pestis ssp. pestis Spatial MLVA25 Genotypic Structure in the Transboundary Saylyugem Natural Plague Focus - M. B. Yarygina; S. A. Vityazeva; V. M. Korzun; H. Tungalag; D. Tserennorov; S. V. Balakhonov (Проблемы особо опасных инфекций, 2023)
Advanced molecular-genetic methods for the diagnosis and typing of Yersinia pestis ssp. pestis in the field and clinical material are used for epidemiological surveillance of plague in the Saylyugem natural focus. The aim of the work was to study the spatial genotypic structure of Y. pestis ssp. pestis in the transboundary Saylyugem natural plague focus using MLVA25 typing. Materials and methods. The MLVA25 typing of 160 strains of Y. pestis ssp. Pestis isolated in the Saylyugem natural plague focus in 2012–2021 was carried out. Phylogenetic tree construction was performed with the help of UPGMA and MST methods. Results and discussion. The Y. pestis ssp. pestis strains isolated from the Saylyugem natural plague focus were differentiated into 15 MLVA types by the 25 VNTR loci cluster analysis. The studied strains form a homogeneous complex of MLVA25 types without marked geographical distribution across seven spatial groups. The analysis of the frequency of occurrence of the tandem repeats number for three variable loci of Y. pestis ssp. pestis strains shows the significant differences between the samples from the Mongolian and Russian parts of the Saylyugem natural plague focus. The most pronounced differences in spatial genotypic structure are traced through the yp4280ms62 locus.